2014
DOI: 10.1292/jvms.14-0272
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotyping of Cryptosporidium spp. in Farm Animals in Egypt

Abstract: In this study, we examined the prevalence and molecular characteristics of Cryptosporidium in buffalo, dairy cattle and sheep in different farms at Kafr El Sheikh Province, Egypt. Rectal fecal samples, including 466 samples from buffalo, 1697 from cattle and 120 from sheep, were collected from different ages and screened by modified Ziehl-Neelsen acid-fast microscopy for detection of Cryptosporidium oocysts. All studied farms were positives with an overall prevalence of 1.29% in buffalo (4.17% in claves versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
4
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 50 publications
4
37
4
2
Order By: Relevance
“…It is difficult to compare the C. parvum prevalence determined in the present study based on ELISA, with previous reports in Egypt where C. parvum infection in farm animals was mostly screened using microscopical observation of fecal oocyst via modified ZiehlNeelsen stain that counts on detecting the current infection (El-Khodery and Osman, 2008, Amer et al, 2010, Amer et al, 2013, Mahfouz et al, 2014. A small number of studies have screened C. parvum in cattle in the Ismailia governorate in the region of the Suez Canal, northeastern Egypt, using commercial ELISA or immunochromatographic assay; however, they focused on detection of the antigen in fecal specimens of suspected animals (Helmy et al, 2013(Helmy et al, , 2014(Helmy et al, , 2015.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is difficult to compare the C. parvum prevalence determined in the present study based on ELISA, with previous reports in Egypt where C. parvum infection in farm animals was mostly screened using microscopical observation of fecal oocyst via modified ZiehlNeelsen stain that counts on detecting the current infection (El-Khodery and Osman, 2008, Amer et al, 2010, Amer et al, 2013, Mahfouz et al, 2014. A small number of studies have screened C. parvum in cattle in the Ismailia governorate in the region of the Suez Canal, northeastern Egypt, using commercial ELISA or immunochromatographic assay; however, they focused on detection of the antigen in fecal specimens of suspected animals (Helmy et al, 2013(Helmy et al, , 2014(Helmy et al, , 2015.…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, antibodies to N. caninum were detected in 7.92% of human samples and 20.43% of cattle in the delta region in Egypt (Ibrahim et al, 2009). Cryptosporidium parvum was sampled in buffalo and dairy cattle on different farms in Kafr El Sheikh Province, northern Egypt, using microscopical examination of fecal samples for detection of Cryptosporidium oocysts, showing that all farms had positive animals, with an overall prevalence of 1.29% in buffalo and 7.07% in cattle (Mahfouz et al, 2014). The C. parvum infection rate in buffalo calves using fecal sample analysis demonstrated a prevalence of 14.19% in Dakahlia and Kafr El Sheikh, northern Egypt (El-Khodery and Osman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, it was known that C. parvum is infectious to many mammalian hosts worldwide (Fayer et al, 2006;Santin and Zarlenga, 2009). Calves were the major recognized reservoirs for C. parvum (Caccio et al, 2000;Warda et al, 2002;Condoleo et al, 2007;Paul et al, 2008;Helmy et al, 2013;Mahfouz et al, 2014) with strong relation between C. parvum infection and diarrhea among Egyptian buffalo calves (Warda et al, 2002). Cryptospordium parvum was mostly dominant in preweaned calves (El-Dessouky and El-Masry, 2005;Santin et al, 2008;Keshavarz et al, 2009;Karanis et al, 2010;Randhawa et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…In buffaloes of different farms at Kafr El Sheikh province, Egypt, PCR-RFLP analyses of small-subunit rRNA genes from positive specimens revealed the occurrence of C. parvum and C. ryanae. Genotypes distribution showed that C. ryanae was the dominant species (60%) followed by C. parvum (40%) in buffalo calves (Mahfouz et al, 2014). This study was aimed to identify Cryptosporidium species isolated from Egyptian buffalo calves and to study the effect of cryptosporidiosis on intestinal tissues referring to its pathological changes.…”
Section: Introductionmentioning
confidence: 99%
“…This species has been detected previously in buffaloes in many countries including Spain, Italy, Australia, Egypt, India, and Thailand (Amer et al 2013;Cacciò et al 2007;Gómez-Couso et al 2005;Maurya et al 2013;Abeywardena et al 2013a;Inpankaew et al 2014;Mahfouz et al 2014;Aquino et al 015). Previous studies have reported that C.…”
Section: Discussionmentioning
confidence: 62%